2016
DOI: 10.1016/j.eurpsy.2016.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Recovery assessment scale: Examining the factor structure of the German version (RAS-G) in people with schizophrenia spectrum disorders

Abstract: The study results are discussed in the light of other studies examining the factor structure of the RAS. Overall, they support the use of the RAS-G as a means to promote recovery oriented services, policies, and research in German-speaking countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
24
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 53 publications
3
24
0
3
Order By: Relevance
“…The lower means on the Goal and success orientation and Reliance on others sub-scales reported by Japanese respondents, as compared to US respondents, was explained by differences in emphasis of aspects of hope, personal confidence and collectivism between Eastern and Western cultures. In the present study mean RAS-R scores appeared similar to the scores reported by Cavelti et al (2017) in their recent study from the German cultural context [ 35 ]. The fact that mean RAS-R responses in the Norwegian context were similar to the responses in the study set in the German context, may reflect similarity in cultures among these two countries.…”
Section: Discussionsupporting
confidence: 91%
“…The lower means on the Goal and success orientation and Reliance on others sub-scales reported by Japanese respondents, as compared to US respondents, was explained by differences in emphasis of aspects of hope, personal confidence and collectivism between Eastern and Western cultures. In the present study mean RAS-R scores appeared similar to the scores reported by Cavelti et al (2017) in their recent study from the German cultural context [ 35 ]. The fact that mean RAS-R responses in the Norwegian context were similar to the responses in the study set in the German context, may reflect similarity in cultures among these two countries.…”
Section: Discussionsupporting
confidence: 91%
“…First of all, our data show that most of the enrolled patients reached the state of recovery and this result is crucial, as it supports that the course of schizophrenia is not inevitably deteriorating . This historic, pessimistic view has progressively changed over recent decades, also thanks to the end of hospitalization and the introduction of new antipsychotics .…”
Section: Discussionsupporting
confidence: 67%
“…In general, recovery can be defined as sustained symptom remission, functional rehabilitation (e.g., cognitive, social, and vocational) and reduced use of medical health services . Whitehorn et al proposed a definition of recovery including autonomous daily living (Global Assessment of Functioning [GAF] score > 50), a normal range of social and occupational functioning (Social and Occupational Functional Assessment score > 60) and a significant reduction of psychopathology (Positive and Negative Syndrome Scale [PANSS] score of ≤4 on all items) .…”
mentioning
confidence: 99%
“…For patients, the baseline assessment will take place before randomisation and include a set of validated questionnaires: PHQ-9,25 GAD-7,12 German version of the Recovery Assessment Scale,40 EQ-5D,41 Somatic Symptom Disorder–B Criteria Scale42 and Patient Assessment of Chronic Illness Care 43. Following the Medical Research Council guidance on developing and evaluating complex interventions,44 a health-economic evaluation is planned for the main trial.…”
Section: Methods and Analysismentioning
confidence: 99%
“…1. Patient Health Questionnaire 9 (PHQ-9),25 Generalised Anxiety Disorder Scale (GAD-7),25 Recovery Assessment Scale (RAS-G),40 EQ-5D,41 Somatic Symptom Disorder–B Criteria Scale (SSD-12) 42. 2.…”
Section: Methods and Analysismentioning
confidence: 99%